PENGEMBANGAN DESAIN MODEL PEMBELAJARAN PAI BERBASIS KARAKTER MULIA YANG HOLISTIK, HUMANIS, EMANSIPATORIS, DAN EFEKTIF - Abudin Nata; Ahmad Sofyan (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
Abstract: Religious education required not only to provide a deep understanding of the religion, but rather should contribute to the community in shaping the character mulia. Many efforts had to meet these demands, but has not shown significant results. This study offers a learning model based on the character of religious education that is holistic noble, humane, and effective emansipatoric, with the steps: Modelling, reflecting, deep discussion, problem solving, socialization and authentic assessment. Based on the results of a descriptive qualitative study in Madrasah Development UIN Syarif Hidayatullah Jakarta, it turns learning model has been implemented, and the results were quite effective in forming a noble character. MP UIN Jakarta, though not yet executed the systematic learning model and be consolidazed, but in fact it has brought learning outcomes that meet the expectations of society. Therefore such a learning model that needs to be strengthened and applied to other educational institutions. DOI: 10.15408/tjems.v1i1.1109